Comparative study on dynamic compressive properties and sustainability assessment of one-part fiber-reinforced geopolymer composites - Hanyuan Shi; Qian Zang; Yingfan Wang; Haimin Qian; Zhouhong Zong; Jingming Cai; Mei Li; Yuanzheng Lin (Case Studies in Construction Materials, 2025)
Although geopolymers can significantly reduce carbon dioxide emissions, their widespread application is limited due to the requirement for alkaline activation solutions. The recently developed “one-part geopolymer” overcomes this limitation by using a solid alkaline activator, thereby enhancing construction convenience while maintaining performance comparable to conventional alkaline solution activated geopolymers or cement-based materials. In this study, a split Hopkinson pressure bar (SHPB) was employed to investigate the dynamic properties of one-part fiber-reinforced geopolymer concrete (OP-FRGC), focusing on different types of fibers. The compressive dynamic increase factor (CDIF), energy absorption capacity, and failure modes of OP-FRGC under dynamic loading were analyzed. The results indicate that the incorporation of fibers changes the failure mode of OP-FRGC from brittle to ductile, significantly enhancing its toughness. OP-FRGC exhibited strain rate sensitivity, with the CDIF showing an approximate logarithmic increase with the strain rate. In addition, a comprehensive evaluation of OP-FRGC incorporating different fiber types was conducted, considering mechanical properties, sustainability, and cost. This study offers a useful reference for understanding the dynamic behavior of OP-FRGC, thereby promoting its potential in practical engineering applications.